Randomized Controlled Trial of Home‐Based Lifestyle Therapy on Postpartum Weight in Underserved Women with Overweight or Obesity. Issue 4 (21st March 2019) - Haire‐Joshu, Debra; Cahill, Alison G.; Stein, Richard I.; Cade, W. Todd; Woolfolk, Candice L.; Moley, Kelle; Mathur, Amit; Schwarz, Cynthia D.; Schechtman, Kenneth B.; Klein, Samuel
Abstract : Objective: This study aimed to assess the efficacy of a home‐based lifestyle intervention delivered through Parents as Teachers (PAT), a national home‐visiting organization, designed to minimize excessive weight gain through 12 months post partum in socioeconomically disadvantaged (SED) African American women with overweight or obesity. Methods: This randomized controlled trial was conducted at a single center as part of the Lifestyle Interventions for Expectant Moms (LIFE‐Moms) consortium. Analysis was conducted with 185 SED African American women (BMI 25.0‐45.0 kg/m 2 at pregnancy onset) retained from an original sample of 267 randomized to standard PAT or PAT+Lifestyle, which embedded lifestyle therapy within standard PAT delivered prenatally and for 12 months post partum. Results: Compared with standard PAT, the PAT+Lifestyle group gained less weight (2.5 kg vs. 5.7 kg; P  = 0.01) and were more likely to return to their baseline weight (38.0% vs. 21.5%; P  = 0.01) from baseline to 12 months post partum. There were no differences between groups in cardiometabolic outcomes, indices of glycemic control and insulin sensitivity, and plasma lipid profile. The estimated cost of PAT+Lifestyle was $81 more to deliver per family than standard PAT. Conclusions: PAT+Lifestyle decreases weight gain during pregnancy through 12 months post partum in SED African American women with overweight or obesity at the start of pregnancy with minimal additional cost.